Measurement of quality services in the laboratory. Issue 4 (April 2020) - Nugraha, N; Mulyati, D S; Bachtiar, I; Nursagita, C
Abstract: The problem in this study is complaints about the quality of laboratory services in the Faculty of Engineering which were delivered by students through a pre-research questioner. This problem needs to be corrected by measuring the quality of laboratory services so that it can increase satisfaction from students. The purpose of this research is to find out student satisfaction with the quality of services in the Faculty of Engineering laboratory. The method used in this study is the Service Quality (SERVQUAL). The results of the research obtained using the SERVQUAL model, the lowest values for each dimension were obtained. Tangible; laboratory room are clean, comfortable and spacious in accordance the standard national laboratory. Empathy; Assistants the Laboratory gives attention and prioritizes. Responsiveness; Assistants provide services quickly and precisely. Reliability; The assessment process is an objective and transparant. The Assurance; Assistant has the ability to answer all practical questions. The conclusion of the research that The priority to improve service quality the dimensions of tangible; laboratory room are clean, comfortable and spacious in accordance the standard national laboratory.